TOBERMORITE-PLOMBIERITE METASOMATITES OF THE GUMESHEVSK SKARN-PORPHYRY COPPER DEPOSIT, MIDDLE URALS - Zadov A.E.; Grabezhev A.I.; Pribavkin S.V.; Pertsev N.N.; Chukanov N.V. (My University, 2006)
Although calcic hydrosilicates with tobermorite-type structure (tobermorite, plombierite, and tacherenite) are rare minerals, they are rather typical of low-temperature mineral assemblages in some Ca-silicate rocks. Owing to defect structure and micrometer-size crystals, minerals of the tobermorite group are studied insufficiently, and each finding attracts interest. Most often, these minerals fill fissures. At the Gumeshevsk skarn–porphyry copper deposit, we detected them as massive metasomatite bodies.